PROLIFERATIVE LEUKEMIC RETINOPATHY WITH BILATERAL EXUDATIVE RETINAL DETACHMENTS AND OPTIC DISC SWELLING IN A PATIENT WITH ACUTE LYMPHOBLASTIC LEUKEMIA - Linda Susanti; Safaruddin Refa; Mirza Metita; Nadia Artha Dewi (Indonesian Vitreoretinal Society, 2019)
Introduction: To report a patient with acute lymphoblastic leukemia (ALL) who developed proliferative leukemic retinopathy with bilateral exudative retinal detachments and optic disc swelling. Case Report: A 11-year-old girl diagnosed with ALL-L2 on maintenance chemotherapy presented with severe blurred vision in both eyes for the past 1 year. Her visual acuity was 0,5/60 for both eyes. Slit-lamp examination of the anterior segment was found normal. Dilated fundus examination revealed tortuous retinal vessels, retinal haemorrhage, retinal and optic disc neovascularizations, optic disc with indistinct margins, and total retinal detachments in both eyes, as well as vitreous haemorrhage in the left eye. The ultrasonography examination revealed bilateral subretinal fluid. Discussion: The patient was diagnosed with bilateral proliferative leukemic retinopathy with exudative retinal detachments and infiltrative optic neuropathy, and left eye vitreous haemorrhage due to ALL. Conservative treatment was given. She continued the maintenance chemotherapy from pediatric department. After 2 months follow up, the visual acuity did not improve although retinal detachments were reduced. There were atrophic changes at the retina of her both eyes. Conclusion: It was reported a rare case of proliferative leukemic retinopathy with bilateral exudative retinal detachments and optic disc swelling. Early recognition and treatment is crucial to improve prognosis.